2011
DOI: 10.1017/s1368980011002059
|View full text |Cite
|
Sign up to set email alerts
|

Measures of the home environment related to childhood obesity: a systematic review

Abstract: Objective: Due to a proliferation of measures for different components of the home environment related to childhood obesity, the purpose of the present systematic review was to examine these tools and the degree to which they can validly and reliably assess the home environment. Design: Relevant manuscripts published between 1998 and 2010 were obtained through electronic database searches and manual searches of reference lists. Manuscripts were included if the researchers reported on a measure of the home envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
102
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(104 citation statements)
references
References 79 publications
1
102
0
1
Order By: Relevance
“…Higher parental education, parental nurturing, and higher self-esteem reduce obesity risk in girls (22). There is an abundance of evidence that the home food environment (23)(24)(25), shared family meals (26,27), and electronic media use influence children's obesity (28) largely through behavioral pathways. Mothers primarily establish the home food environment and are role models for eating behaviors (29) with evidence of strong correlation between the eating patterns of mothers and children (25,29).…”
Section: Introductionmentioning
confidence: 99%
“…Higher parental education, parental nurturing, and higher self-esteem reduce obesity risk in girls (22). There is an abundance of evidence that the home food environment (23)(24)(25), shared family meals (26,27), and electronic media use influence children's obesity (28) largely through behavioral pathways. Mothers primarily establish the home food environment and are role models for eating behaviors (29) with evidence of strong correlation between the eating patterns of mothers and children (25,29).…”
Section: Introductionmentioning
confidence: 99%
“…Three reviews on the home environment and its importance for childhood obesity, on dietary weight-loss interventions in people of African ancestry and on free will and the obesity epidemic are also included in this issue (15)(16)(17) .…”
mentioning
confidence: 99%
“…The list included statements associated with health issues (31,33,34) , parental control of child feeding (11,29,30) and aspects of the home environment (11,30,32,33,35) . In multiple cases, extracted items were found on more than one source as also noted by Pinard et al (26) in their systematic review which revealed overlapping constructs assessed on different measures.…”
Section: Instrument Developmentmentioning
confidence: 73%
“…Researchers have also considered other frameworks with KAB-framed interventions among different groups, such as the transtheoretical model (23) and self-efficacy constructs (24,25) . Despite the availability of parent questionnaires to assess nutrition education, a systematic review by Pinard et al showed that use of these tools is limited by the lack of psychometric assessment and the topic thus merits further research (26) .…”
mentioning
confidence: 99%